Efficacy of Oclacitinib on Feline Atopic Syndrome Management - Rocha Fernandes, Keylla Suellen Batalha; Ferreira, Mirlla Baracho; da Silva, Alessandra Moreira; Marques, Kayana Cunha; Lopes Rocha, Brizza Zorayd Luz; Bezerra, José Artur Brilhante; Filgueira, Kilder Dantas (Acta Scientiae Veterinariae, 2019)
Background: The feline atopic syndrome (FAS) associated to environmental allergens is the third most common allergic dermatosis in domestic cats. In general, clinical signs are not pathognomonic and the exclusion of other pruritus causes is necessary to reach the diagnosis of FAS. The treatment is based on the use of drugs to control the pruritus, such as glucocorticoids, cyclosporine and, recently, oclacitinib, a Janus kinase inhibitor. This study aimed to report the efficacy of oclacitinib on the treatment of FAS associated to environmental allergens. Case: A 10-year-old female feline, crossbred, presented a history of pruritic dermatitis during ten months and diarrhea. The animal had been submitted to treatment for ectoparasites with pour-on selamectin and was fed with a commercial hypoallergenic diet in the last eight weeks or so. However, no improvement on the skin condition was observed. Physical examination revealed disseminated furfuraceous desquamation, excoriation and erythema on the right supraorbital region. Bilateral conjunctivitis was also observed. Complete blood cell count, biochemistry profile, urinalysis, immunochromathographic test for feline immunodeffiency virus (FIV) and feline leukemia virus (FeLV), fungic culture and abdominal ultrasonography were requested. The abnormalities observed were reduced urinary density and discrete loss of renal corticomedullary differentiation. Thus, based on physical examination and complementary exams, the animal was diagnosis with FAS, since the main other causes of pruritus (hypersensitivity to ectoparasites and alimentary allergens) were excluded. The animal was also diagnosed with stage 1 chronic kidney disease. Therapy based on oclacitinib was instituted with an induction dose of 1 mg/kg twice daily for 14 days, followed by a maintenance dose of 1 mg/kg once daily. After 30 days of treatment, a satisfactory therapeutic response was observed, with complete remission of pruritus. The animal was regularly evaluated, with clinical and laboratorial exams, to check the efficacy of treatment and to identify the possible adverse effects of the drug. After 300 days of treatment the animal presented a relapse of pruritic dermatitis, and the dose was changed to 1 mg/kg twice daily, with remission of clinical signs. No adverse reactions or changes in laboratorial exams were observed during the follow-up, and the chronic kidney disease remained on stage 1. Discussion: In spite of being the third most frequent allergic dermatopathy in cats, FAS is still considered as an uncommon disease. FAS is a diagnosis of exclusion, where hypersensivity to ectoparasites and alimentary allergens must be investigated before reaching the diagnosis of FAS. Clinical signs are not pathognomonic. Thus, pruritus, skin lesions on head and/or neck, miliaris dermatitis, symmetric alopecia and eosinophilic dermatitis can be observed. Other dermatologic and systemic manifestations, such as gastrointestinal, ophthalmic and respiratory signs, may be present. The reported animal presented dermatologic and systemic signs of FAS, since all the clinical alterations disappeared with the use of oclacitinib. Because some dogs demonstrated immunosuppression and developed diseases related to this, such as papilomatosis and demodicosis, while using this drug, we decided to rule out the presence of the infection by FIV and FeLV, before the beginning of the therapy. Other drugs can be used for treat cats with FAS, such as glucocorticoids and ciclosporin. However, these drugs are associated to side effects in a long-term therapy. In this case report, a cat treated with oclacitinib showed a long-term control of pruritus and clinical signs remission without adverse effects. Oclacitinib demonstrated to be a good therapeutic option on the treatment of FAS associated to environmental allergens.